2004
DOI: 10.1002/macp.200300065
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐Induced cis‐to‐trans Isomerization of Poly[(p‐methylthiophenyl)acetylene] Prepared with a [Rh(norbornadiene)Cl]2 Catalyst – A Raman, UV‐Vis, and ESR Study

Abstract: Summary: A stereospecific polymerization of a novel aromatic acetylene containing an alkyl sulfide group, i.e., (p‐methylthiophenyl)acetylene (pMeSPA) was successfully performed to selectively give the corresponding polymer bearing a cis‐transoid structure as a main geometrical form and a very high molecular weight, $\overline M _{\rm n}$ = 1.7–5.8 × 106 in high yields. This was accomplished when a Rh complex catalyst, [Rh(norbornadiene)Cl]2, was used in the presence of triethylamine (TEA) solvent as a cocatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In other words, the spectrum center should be shifted to the fairly lower magnetic field giving a large g value when a hetero atom such as halogen is included in the polymer molecules (see Table 3). It is also noteworthy, therefore, that even in the ESR spectrum of other aromatic polyacetylenes having a hetero atom other than halogen, two peaks may be separately observed as those of cis and trans geometrical isomers when the pristine cis polymer was prepared with the Rh complex catalyst under quite mild polymerization conditions followed by compression as reported before 27,28. As we have already shown above when the PpIPA was compressed we can have two ESR peaks which are assigned to the cis and trans radicals.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…In other words, the spectrum center should be shifted to the fairly lower magnetic field giving a large g value when a hetero atom such as halogen is included in the polymer molecules (see Table 3). It is also noteworthy, therefore, that even in the ESR spectrum of other aromatic polyacetylenes having a hetero atom other than halogen, two peaks may be separately observed as those of cis and trans geometrical isomers when the pristine cis polymer was prepared with the Rh complex catalyst under quite mild polymerization conditions followed by compression as reported before 27,28. As we have already shown above when the PpIPA was compressed we can have two ESR peaks which are assigned to the cis and trans radicals.…”
Section: Resultsmentioning
confidence: 56%
“…It is also noteworthy, therefore, that even in the ESR spectrum of other aromatic polyacetylenes having a hetero atom other than halogen, two peaks may be separately observed as those of cis and trans geometrical isomers when the pristine cis polymer was prepared with the Rh complex catalyst under quite mild polymerization conditions followed by compression as reported before. [27,28] As we have already shown above when the PpIPA was compressed we can have two ESR peaks which are assigned to the cis and trans radicals. Therefore, if two points using the g values, 2.0067 and 2.0024 due to cis and trans radicals are depicted in the Figure 5 and these points were connected with the vertical line at g % 2.0024 we will be able to deduce the cis or trans geometries of the compressed polymer.…”
Section: After Compressionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previously we reported19, 20, 27–31, 33, 34, 43, 50 that the g value of not only aromatic but also aliphatic poly(acetylene)s, such as poly(alkylpropiolate)s, called poly(acetyleneester)s can be used to deduce the reasonable geometrical conformations, that is, cis form or trans form, when one hetero atom such as an O, N, or S is involved within the side chain of the polymer. Such a hetero atom is reported to have a relatively large spin orbit coupling constant (δ)51, 52 compared with the case of the hydrocarbon radicals.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the helical cis ‐transoid isomer is successfully obtained in high yields under quite mild conditions when triethylamine (TEA), an alcohol, and water having an electron donating property due to one or two lone pairs are used as the polymerization solvent 25. Recently, we also found that poly( p ‐methoxyphenyl)acetylene (P p MeOPA),30 and poly( p ‐methylthiophenyl)acetylene (P p MeSPA)31 prepared with the Rh complex, can be easily isomerized from the cis form to the trans form, when the cis ‐polymer powder was compressed under pressure at room temperature, although thermal‐induced cis ‐to‐ trans isomerization associated with a large number of increase in the radical concentration has been considered to take place in such aromatic poly(acetylene)s 14–17…”
Section: Introductionmentioning
confidence: 99%